L'homme entre le geste et le tic - Pintarič, Miha (Vestnik za tuje jezike, 2015)
The article tries to define the relation between the antinomic pairs of expressions, word-silence and gesture-tic, which, each in its own way (verbal or not), determine human communication, which finally translates one's relation to oneself.
Keywords: komunikacija; filozofija jezika; pesniški jezik